An overview of solvent extraction processes developed in Europe for advanced nuclear fuel recycling, Part 2 — homogeneous recycling. Issue 11 (24th July 2022) - Lyseid Authen, Thea; Adnet, Jean-Marc; Bourg, Stéphane; Carrott, Michael; Ekberg, Christian; Galán, Hitos; Geist, Andreas; Guilbaud, Philippe; Miguirditchian, Manuel; Modolo, Giuseppe; Rhodes, Chris; Wilden, Andreas; et al.
ABSTRACT: The hydrometallurgical separation concepts for the recycling of irradiated nuclear fuels developed in Europe are presented and discussed. Whilst Part 1 of the review focused on concepts for heterogeneous recycling of minor actinides, this article focuses on group recycling of transuranic actinides, which would support homogeneous recycling scenarios. Most of these concepts were developed within European collaborative projects and involve solvent extraction processes separating all the actinides (U-Cm) in two cycles. The first cycle uses a monoamide extractant to recover uranium leaving all the transuranic actinides in the aqueous raffinate with the fission products. The second cycle aims for a group recovery of the transuranium elements and several strategies have been proposed for this stage. In this review article, the various solvent extraction processes are summarised and the key features of the process schemes are compared.